The impact of CRM dimensions on call center performance - Abdullateef, Aliyu Olayemi; Mohd Mokhtar, Sany Sanuri; Yusoff, Rushami Zien (Dr. Sang H. Lee, 2010)
This research aims at developing a conceptual framework and valid prepositions on the impacts of Customer Relationship Management (CRM) dimensions on call center performance. The researchers primarily used qualitative approach that involves initial qualitative interview and detailed literature reviews of academic literatures and industry reports on CRM and customer contact centers.Evidence from the extant literatures and the call center managers interviewed suggested that there exist positive relationship between CRM dimensions, perceived service quality, inbound first call resolution and caller satisfaction.Based on these findings, this study proposed a conceptual framework through which the impact of CRM on inbound call center performance can be measured. Given that this paper is based on qualitative approach, there is need to embark on empirical data gathering to validate the conceptual model presented.Very important in this research is that it avails academics the knowledge of the theoretical linkages that exist between CRM dimensions and inbound call center operations.It equally provides opportunity to the contact center management on the benefits that are inherent in measuring the impact of CRM dimensions on perceived service quality, inbound first call resolution and caller satisfaction.